2000
DOI: 10.1177/136346150003700406
|View full text |Cite
|
Sign up to set email alerts
|

Stambali: Dissociative Possession and Trance in a Tunisian Healing Dance

Abstract: This study investigated Stambali, a Tunisian trance-dance practiced in Israel as a healing and a demon exorcism ritual by Jewish-Tunisian immigrants. The authors observed the ritual and conducted semi-structured ethnographic interviews with key informants. Content analysis revealed that Stambali is practiced for prophylactic reasons (e.g. repelling the ‘evil eye’), for the promotion of personal well-being, and as a form of crisis intervention. Crisis was often construed by our informants as the punitive action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 26 publications
0
24
0
2
Order By: Relevance
“…Dances in which the participant (often a woman) enters into a trance and may lose consciousness have been used in a therapeutic setting (e.g., to dispossess “demons”) in diverse cultures, including a North African Jewish community [48]. We suggest the notion that the association we observe between SLC6A4 and dance is perhaps related to the need for altered consciousness states that subjects participating in and performing this art form sometimes have.…”
Section: Discussionmentioning
confidence: 91%
“…Dances in which the participant (often a woman) enters into a trance and may lose consciousness have been used in a therapeutic setting (e.g., to dispossess “demons”) in diverse cultures, including a North African Jewish community [48]. We suggest the notion that the association we observe between SLC6A4 and dance is perhaps related to the need for altered consciousness states that subjects participating in and performing this art form sometimes have.…”
Section: Discussionmentioning
confidence: 91%
“…An ethnographic study by Somer and Saadon [30] described Stambali, a trance dance practiced in Israel by Tunisian-Jewish immigrants, as a prophylactic anxiolytic activity (eg, to deter the ''evil eye'') and as a healing ritual. Stambali is performed for the promotion of personal well-being or as a crisis intervention technique.…”
Section: Kinetically Induced Dissociationmentioning
confidence: 99%
“…Developing countries are not the exclusive terrain of possession disorders and exorcism practices. Reports on these conditions were based on observations from countries in North America [63][64][65] and Latin America [66], the United Kingdom [67], Switzerland [68], Italy [69], France [70], Greece [71], Israel [30,72,73], Korea [74], and Russia [75]. A Barna Research poll showed that 54% of adult Americans believe that ''a human being can be under the control or the influence of spiritual forces such as demons'' [76].…”
Section: Possession Trance and Religionmentioning
confidence: 99%
“…The rituals are normally conducted by representatives of male-dominated religion and society, such as shamans, mystics, rabbis, imams, or Muslim clergy and psychics (Grisaru, Budowski, & Witztum, 1997). Some rituals documented in Israel among Jews from North African descent have been influenced by black African traditions and often involve rhythmic movements and dance accompanied by drum beats (Somer & Saadon, 2000). The desired result is typically a hypnotic trance, which reaches a peak with convulsive movements and loss of memory.…”
Section: Introductionmentioning
confidence: 99%
“…These loci of control are regarded as Dybbuks (Somer, 1997a, Jinns, spirits or the acts of God (Bilu, 1987(Bilu, , 2000. To deal with these conditions, there is a need to appease God or the possessing agents or to confront them with invocations of God's powers by calling on him and invoking his holy names (Somer & Saadon, 2000). The rituals are normally conducted by representatives of male-dominated religion and society, such as shamans, mystics, rabbis, imams, or Muslim clergy and psychics (Grisaru, Budowski, & Witztum, 1997).…”
Section: Introductionmentioning
confidence: 99%